Effects of hydrogen peroxide (H2O2) elicitation on protein content and digestibility, phenolic compounds, and antioxidant activity in sprouted chickpeas (Cicer arietinum L.) - Alejandra Linares-Castañeda; Cristian Jiménez-Martínez; Ana Elena Cedillo-Olivos; Yair Cruz-Narváez; Luis Jorge Corzo-Ríos (Applied Food Research)
Chickpea consumption may be beneficial in the prevention of chronic degenerative diseases due to the presence of bioactive compounds. Sprouting and elicitation have been suggested as methods to enhance the nutritional and biofunctional properties of legumes. This study aims to evaluate the effect of hydrogen peroxide (H2O2) as an elicitor, the soaking time, and sprouting time in days, in the nutritional quality and biofunctional compounds (phenolic compounds) with antioxidant properties in chickpeas. The Box-Behnken design was used to determine the optimal soaking time, elicitor concentration, and sprouting time to maximize protein content, in vitro protein digestibility (IVPD), total phenolic content (TPC) and antioxidant activity (AOX). The optimal germination conditions were soaking for 3 h in 34.34 mM H2O2 and sprouting for 5 days, with maximal protein content (24.39 %) and IVPD (96.29 %), TPC (206.73 mg GAE/100 g) and AOX (121.18 μmol TE/100 g). These results were significantly higher than those from sprouting without elicitors and raw seeds, demonstrating that germination combined with elicitors enhances legume flours biofunctionality and nutritional quality.